2023
DOI: 10.18421/tem124-26
|View full text |Cite
|
Sign up to set email alerts
|

Human Machine Interface-Based Control Training Kit as Innovative Learning Media to Enhance Students’ Automation Control Skills in the Industry 4.0 Era

Aswardi Aswardi,
Doni Tri Putra Yanto,
Citra Dewi
et al.

Abstract: This research investigates the effectiveness of the Human-Machine Interface-based control (HMI-BC) training kit as an innovative learning media in enhancing the Automation Control Skills (ACSs) of Industrial Electrical Engineering (IEE) students in the Industry 4.0 Era. The study focuses on evaluating the students' ACSs in the Electrical Machine Control Course (EMCC) after using the HMI-BC training kit as a practical learning media. The research adopts a quasi-experimental design with a One-Group Pre-test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Students make substantial advances in their abilities, making them more capable and prepared to face difficulties in electric motor control systems in practical situations. This finding is consistent with previous research showing the beneficial effects of tailor-made training aids for the learning process on student aptitude [4]. Even though some research indicated a moderate impact, the aggregate results nonetheless demonstrated the advantages of raising pupils' skill levels [13], [14], [30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Students make substantial advances in their abilities, making them more capable and prepared to face difficulties in electric motor control systems in practical situations. This finding is consistent with previous research showing the beneficial effects of tailor-made training aids for the learning process on student aptitude [4]. Even though some research indicated a moderate impact, the aggregate results nonetheless demonstrated the advantages of raising pupils' skill levels [13], [14], [30].…”
Section: Discussionsupporting
confidence: 91%
“…Using the Levene analysis technique, homogeneity testing was done simultaneously on post-test data from the control and experimental classes. The conclusion of the homogeneity test can be drawn: if the p-value obtained is more significant than 0.05, then the data is declared homogeneous, and if the p-value obtained is smaller than 0.05, then the data is declared inhomogeneous [4]. The findings of the homogeneity analysis are displayed in Table 5.…”
Section: N V O T E Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-experimental research with a one-group pre-test and post-test research design was the research approach utilized in the execution of this investigation, where this research method only uses one class (an experiment) as the research subject, and there is no control class (Aswardi et al, 2023).…”
Section: Design Of Researchmentioning
confidence: 99%
“…The trainer kit can serve as a solution to address obstacles in the learning process, offering a more tangible learning experience and motivating students to actively participate in their learning [19], [20]. Previous research indicates that trainer kits are valid [9], practical [21], and enhance student learning outcomes [22] as learning tools in higher education.…”
Section: Introductionmentioning
confidence: 99%